2018
DOI: 10.1016/j.jtho.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Italian Nivolumab Expanded Access Program in Nonsquamous Non–Small Cell Lung Cancer Patients: Results in Never-Smokers and EGFR-Mutant Patients

Abstract: The data on the Italian expanded access program in populations with nonsquamous NSCLC suggest that subgroups of patients could benefit differently from nivolumab according to their EGFR mutational status and smoking habits. These results warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 24 publications
6
66
1
Order By: Relevance
“…Several studies have shown that NSCLC patients who are smokers and have wild-type EGFR were able to benefit the most from anti-PD-1 therapy. [43][44][45][46][47] Therefore, anti-PD-1 therapy may be the most beneficial for patients with abundant macrophage infiltration. Our findings provide a new potential strategy for priority population selection for anti-PD-1/PD-L1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that NSCLC patients who are smokers and have wild-type EGFR were able to benefit the most from anti-PD-1 therapy. [43][44][45][46][47] Therefore, anti-PD-1 therapy may be the most beneficial for patients with abundant macrophage infiltration. Our findings provide a new potential strategy for priority population selection for anti-PD-1/PD-L1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the IMpower 150 trial (see Recommendation 5, first-line treatment of NSCLC without a druggable oncogene driver) [102], which included data on patients with EGFR or ALK genetic alterations, support the use of a combination of atezolizumab (anti-PD-L1) and bevacizumab with carboplatin and paclitaxel as a therapeutic option in patients with non-squamous mNSCLC, and a PS of 0-1, in the absence of contraindications to the use of immunotherapy and may be an option also in the second-line setting [IV, C] (Figure 3). However, following the meeting in Guangzhou, two publications [192,193] reported a lack of efficacy for ICT mAbs as single-agents second-line, in TKI naive, PD-L1þ, EGFRmutant patients with advanced NSCLC, including those with PD-L1 expression 50%. These data suggest that these agents may not be an appropriate therapeutic choice in this setting.…”
Section: T1mimentioning
confidence: 99%
“…42 The activity and safety of nivolumab in routine clinical practice was also investigated in three different expanded access programs (EAPs) in Canada, France, and Italy, including a pretreated PS 2 population. [43][44][45] Although the safety profile evaluating TRAEs and TRAEs leading to discontinuation was comparable with the overall population, median survival was worse in patients with ECOG PS 2 (Canadian EAP: 5.9 v 9.1 months; Italian EAP: PS 2 was a predictive factor for both PFS and OS). 43,45 However, all these studies just proved that PS 2 patients have a poorer prognosis than patients with PS 0 or 1, consistent with prior knowledge.…”
mentioning
confidence: 99%